From Farm to Fork : Private Enterprise Can Reduce Food Loss through Climate-Smart Agriculture - Mills, Anthony (International Finance Corporation, Washington, DC, 2018)
More than a billion tons of food are lost annually across global food supply chains. Spillage, spoilage, insects, and rodents cause this post-harvest loss. Addressing it is a daunting challenge due to the complexity of the many factors involved. But it is a worthwhile challenge because of the potential benefits, including improved food security, nutrition, economic productivity, and response to climate change. Poor or nonexistent public infrastructure is often an underlying cause of food not being transported or processed effectively. And climate change damages existing infrastructure and increases losses. Despite the numerous environmental, economic, and socio-cultural barriers involved, there are many examples of private sector enterprises that have tackled post-harvest loss successfully. They focus on education, collaboration, and markets. Intense analyses by multi-disciplinary teams will need to be conducted on socio-cultural factors, as well as consideration of appropriate technologies to address post-harvest food losses, the economic opportunities involved, and the likely climate change impacts.